Low-cost workbench client / server cores for remote experiments in electronics - José M. M. Ferreira (2010)
This paper offers an open-source solution to implement low-cost workbenches serving a wide range of remote experiments in electronics. The proposed solution comprises 1) a small (9,65 x 6,1 cm) Linux server board; 2) a server core supporting two TCP/IP communication channels, and general purpose I/O pin drivers to interface the remote experiment hardware; and 3) a client core based on a multi-tab user interface supporting text file management to exchange experiment scripts / status information, and a mini-browser for webcasting in distance learning scenarios, live image feedback from IP cameras located in the remote workbench, etc. Additional drivers and application-specific tabs can be added to the server / client cores, to suit the requirements of each application. Two remote workbenches for microcontroller and digital systems testing courses were developed, and are also presented in this document.